2021
DOI: 10.1111/tid.13595
|View full text |Cite
|
Sign up to set email alerts
|

Effect of immunosuppression maintenance in solid organ transplant recipients with COVID‐19: Systematic review and meta‐analysis

Abstract: Background The aim of this study was to assess the effect of continuing immune suppressive therapy in solid organ transplant recipients (SOTR) with coronavirus disease 2019 (COVID‐19). Methods Systematic review and meta‐analysis of data on 202 SOTR with COVID‐19, published as case reports or case series. We extracted clinical, hemato‐chemical, imaging, treatment, and outcome data. Results Most patients were kidney recipients (61.9%), males (68.8%), with median age of 57 years. The majority was on tacrolimus (7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 97 publications
(120 reference statements)
0
18
0
2
Order By: Relevance
“…In a recently published systematic review and meta-analysis, maintaining immunosuppression was concluded to be safe in SOT recipients with moderate or severe COVID-19, and continuing tacrolimus was suggested to be beneficial. 31 Additional evidence to support concrete guidance on the management of immunosuppression in SOT recipients diagnosed with COVID-19 is needed.…”
Section: Discussionmentioning
confidence: 99%
“…In a recently published systematic review and meta-analysis, maintaining immunosuppression was concluded to be safe in SOT recipients with moderate or severe COVID-19, and continuing tacrolimus was suggested to be beneficial. 31 Additional evidence to support concrete guidance on the management of immunosuppression in SOT recipients diagnosed with COVID-19 is needed.…”
Section: Discussionmentioning
confidence: 99%
“…However, their study included only 125 renal transplant recipients and was based generally on case reports or case series. 48 While possibly beneficial during the acute COVID‐19 due to the anti‐inflammatory effect, tacrolimus may be associated with an additional endothelial injury 49 , 50 induced by SARS‐CoV‐2. Further studies are needed to clarify these results.…”
Section: Discussionmentioning
confidence: 99%
“…A recently published meta‐analysis that included 202 solid organ transplant recipients concluded that receiving tacrolimus could benefit COVID‐19. However, their study included only 125 renal transplant recipients and was based generally on case reports or case series 48 . While possibly beneficial during the acute COVID‐19 due to the anti‐inflammatory effect, tacrolimus may be associated with an additional endothelial injury 49,50 induced by SARS‐CoV‐2.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of data on 202 SOT recipients with COVID-19 suggested that maintaining immunosuppression might be safe in moderate and severe COVID-19. Moreover, tacrolimus could be specifically beneficial [ 138 ].…”
Section: Therapeutic Options In Sot Recipients In Covid-19mentioning
confidence: 99%